Neuronal Dysfunction Associated with Cholesterol Deregulation. - Marcuzzi, Annalisa; Loganes, Claudia; Valencic, Erica; Piscianz, Elisa; Monasta, Lorenzo; Bilel, Sabrine; Bortul, Roberta; Celeghini, Claudio; Zweyer, Marina; Tommasini, Alberto (Int J Mol Sci, 2018)
Cholesterol metabolism is crucial for cells and, in particular, its biosynthesis in the central nervous system occurs in situ, and its deregulation involves morphological changes that cause functional variations and trigger programmed cell death. The pathogenesis of rare diseases, such as Mevalonate Kinase Deficiency or Smith⁻Lemli⁻Opitz Syndrome, arises due to enzymatic defects in the cholesterol metabolic pathways, resulting in a shortage of downstream products. The most severe clinical manifestations of these diseases appear as neurological defects. Expanding the knowledge of this biological mechanism will be useful for identifying potential targets and preventing neuronal damage. Several studies have demonstrated that deregulation of the cholesterol pathway induces mitochondrial dysfunction as the result of respiratory chain damage. We set out to determine whether mitochondrial damage may be prevented by using protective mitochondria-targeted compounds, such as MitoQ, in a neuronal cell line treated with a statin to induce a biochemical block of the cholesterol pathway. Evidence from the literature suggests that mitochondria play a crucial role in the apoptotic mechanism secondary to blocking the cholesterol pathway. Our study shows that MitoQ, administered as a preventive agent, could counteract the cell damage induced by statins in the early stages, but its protective role fades over time.
Keywords: Anticholesteremic Agents; Cell Line, Tumor; Cholesterol; Electron Transport; Humans; Lovastatin; Mitochondria; Neurons; Neuroprotective Agents; Organophosphorus Compounds; Ubiquinone

Pre-eclampsia affects procalcitonin production in placental tissue. - Agostinis, Chiara; Rami, Damiano; Zacchi, Paola; Bossi, Fleur; Stampalija, Tamara; Mangogna, Alessandro; Amadio, Leonardo; Vidergar, Romana; Vecchi Brumatti, Liza; Ricci, Giuseppe; Celeghini, Claudio; Radillo, Oriano; et al. (Am J Reprod Immunol, 2018)
PROBLEM: Procalcitonin (PCT) is the prohormone of calcitonin which is usually released from neuroendocrine cells of the thyroid gland (parafollicular) and the lungs (K cells). PCT is synthesized by almost all cell types and tissues, including monocytes and parenchymal tissue, upon LPS stimulation. To date, there is no evidence for PCT expression in the placenta both in physiological and pathological conditions. METHOD: Circulating and placental PCT levels were analysed in pre-eclamptic (PE) and control patients. Placental cells and macrophages (PBDM), stimulated with PE sera, were analysed for PCT expression. The effect of anti-TNF-α antibody was analysed. RESULTS: Higher PCT levels were detected in PE sera and in PE placentae compared to healthy women. PE trophoblasts showed increased PCT expression compared to those isolated from healthy placentae. PE sera induced an upregulation of PCT production in macrophages and placental cells. The treatment of PBDM with PE sera in the presence of anti-TNF-α completely abrogated the effect induced by pathologic sera. CONCLUSION: Trophoblast cells are the main producer of PCT in PE placentae. TNF-α, in association with other circulating factors present in PE sera, upregulates PCT production in macrophages and normal placental cells, thus contributing to the observed increased in circulating PCT in PE sera.
Keywords: Adult; Calcitonin; Cohort Studies; Female; Humans; Macrophages; Placenta; Pre-Eclampsia; Pregnancy; Trophoblasts; Tumor Necrosis Factor-alpha; Up-Regulation; Young Adult

Repositioning of Tak-475 In Mevalonate Kinase Disease: Translating Theory Into Practice. - Marcuzzi, Annalisa; Loganes, Claudia; Celeghini, Claudio; Kleiner, Giulio (Curr Med Chem, 2018)
BACKGROUND: Mevalonate Kinase Deficiency (MKD, OMIM #610377) is a rare autosomal recessive metabolic and inflammatory disease. In MKD, defective function of the enzyme mevalonate kinase, due to a mutation in the MVK gene, leads to the shortage of mevalonate- derived intermediates, which results in unbalanced prenylation of proteins and altered metabolism of sterols. These defects lead to a complex multisystem inflammatory and metabolic syndrome. OBJECTIVE: Although biologic therapies aimed at blocking the inflammatory cytokine interleukin- 1 can significantly reduce inflammation, they cannot completely control the clinical symptoms that affect the nervous system. For this reason, MKD can still be considered an orphan drug disease. The availability of MKD models reproducing the MKD-systematic inflammation, is crucial to improve the knowledge on its pathogenesis, which is still unknown. New therapies are also required in order to improve pateints' conditions and their quality of life. METHODS: MKD-cellular models can be obtained by biochemical inhibition of mevalonatederived isoprenoids. Of note, these cells present an exaggerated response to inflammatory stimuli that can be reduced by treatment with zaragozic acid, an inhibitor of squalene synthase, thus increasing the availability of isoprenoids intermediates upstream the enzymatic block. RESULTS: A similar action might be obtained by lapaquistat acetate (TAK-475, Takeda), a drug that underwent extensive clinical trials as a cholesterol lowering agent 10 years ago, with a good safety profile. CONCLUSIONS: Here we describe the preclinical evidence supporting the possible repositioning of TAK-475 from its originally intended use to the treatment of MKD and discuss its potential to modulate the mevalonate pathway in inflammatory diseases.
Keywords: Acyl Coenzyme A; Cholesterol; Drug Repositioning; Farnesyl-Diphosphate Farnesyltransferase; Humans; Hypercholesterolemia; Mevalonate Kinase Deficiency; Oxazepines; Phosphotransferases (Alcohol Group Acceptor); Piperidines

Geranylgeraniol and Neurological Impairment: Involvement of Apoptosis and Mitochondrial Morphology. - Marcuzzi, Annalisa; Piscianz, Elisa; Zweyer, Marina; Bortul, Roberta; Loganes, Claudia; Girardelli, Martina; Baj, Gabriele; Monasta, Lorenzo; Celeghini, Claudio (Int J Mol Sci, 2016)
Deregulation of the cholesterol pathway is an anomaly observed in human diseases, many of which have in common neurological involvement and unknown pathogenesis. In this study we have used Mevalonate Kinase Deficiency (MKD) as a disease-model in order to investigate the link between the deregulation of the mevalonate pathway and the consequent neurodegeneration. The blocking of the mevalonate pathway in a neuronal cell line (Daoy), using statins or mevalonate, induced an increase in the expression of the inflammasome gene (NLRP3) and programmed cell death related to mitochondrial dysfunction. The morphology of the mitochondria changed, clearly showing the damage induced by oxidative stress and the decreased membrane potential associated with the alterations of the mitochondrial function. The co-administration of geranylgeraniol (GGOH) reduced the inflammatory marker and the damage of the mitochondria, maintaining its shape and components. Our data allow us to speculate about the mechanism by which isoprenoids are able to rescue the inflammatory marker in neuronal cells, independently from the block of the mevalonate pathway, and about the fact that cell death is mitochondria-related.

Design, Synthesis, and Biological Characterization of Novel Mitochondria Targeted Dichloroacetate-Loaded Compounds with Antileukemic Activity. - Trapella, Claudio; Voltan, Rebecca; Melloni, Elisabetta; Tisato, Veronica; Celeghini, Claudio; Bianco, Sara; Fantinati, Anna; Salvadori, Severo; Guerrini, Remo; Secchiero, Paola; Zauli, Giorgio (J Med Chem, 2015)
The mitochondrial kinase inhibitor dichloroacetate (DCA) has recently received attention in oncology due to its ability to target glycolysis. However, DCA molecule exhibits poor bioavailability and cellular uptake with limited ability to reach its target mitochondria. To overcome these biases, we have synthesized novel DCA-loaded compounds. The selection of the most promising therapeutic molecule was evaluated by combining in vitro assays, to test the antitumoral potential on leukemic cells, and a preliminary characterization of the molecule stability in vivo, in mice. Among the newly synthesized compounds, we have selected the multiple DCA-loaded compound 10, characterized by a tertiary amine scaffold, because it exhibited enhanced (>30-fold) in vitro antitumor activity with respect to DCA and increased in vivo stability. On the basis of these results, we believe that compound 10 should be considered for further preclinical evaluations for the treatment of cancers and/or other diseases characterized by altered metabolic origin.

TNF-related apoptosis inducing ligand in ocular cancers and ocular diabetic complications. - Perri, Paolo; Zauli, Giorgio; Gonelli, Arianna; Milani, Daniela; Celeghini, Claudio; Lamberti, Giuseppe; Secchiero, Paola (Biomed Res Int, 2015)
TNF-related apoptosis inducing ligand (TRAIL) is an intensively studied cytokine, in particular for its anticancer activity. The discovery that conjunctival sac fluid contains extremely high levels of soluble TRAIL as compared to other body fluids suggested important implications in the context of the immunological surveillance of the eye, in particular of the anterior surface. In this review, we discuss the potential physiopathologic and therapeutic role of the TRAIL/TRAIL receptor system in a variety of ocular cancers. Moreover, since an increasing amount of data has indicated the important biological activities of the TRAIL/TRAIL receptor systems also in a completely different pathologic context such as diabetes mellitus, in the second part of this review we summarize the currently available data on the involvement of TRAIL in the ocular complications of diabetes mellitus as modulator of the inflammatory and angiogenic response in the eye.
Keywords: Apoptosis; Diabetes Complications; Diabetes Mellitus; Eye Neoplasms; Humans; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand

Association of serum tumor necrosis factor-related apoptosis inducing ligand with body fat distribution as assessed by dual X-rays absorptiometry. - Cervellati, Carlo; Secchiero, Paola; Bonaccorsi, Gloria; Celeghini, Claudio; Zauli, Giorgio (Mediators Inflamm, 2014)
A low chronic inflammation mediated by cytokine release is considered a major pathogenic mechanism accounting for the higher risk of cardiovascular disease in the overweight/obese population. In this context, although the existence of a possible interaction between soluble tumor necrosis factor- (TNF-) related apoptosis inducing ligand (TRAIL) and quantity and localization, of adiposity in the body has been hypothesized, no studies have yet investigated this link by radiologic techniques able to assess directly fat mass (FM) in different body regions. To address this issue, we assessed body fat distribution by dual X-rays absorptiometry (DXA) in a sample of 103 women and investigated the possible association between the derived adiposity measures and serum TRAIL concentration. The level of TRAIL showed a positive and independent correlation with arms FM (P < 0.05), trunk FM (P < 0.001) and trunk FM% (P < 0.05), total FM and total FM% (P < 0.001 for both), and an inverse association with legs FM% (P < 0.05). Only trunk FM retained a significant correlation (P < 0.05) with TRAIL after adjusting for all the other indices of regional adiposity. In conclusion, from our study it emerged a significant and independent association of serum TRAIL levels with overall, and, mainly, central adiposity. Further studies are needed to longitudinally investigate the cause-effect relationship between change in body fat distribution and TRAIL.
Keywords: Absorptiometry, Photon; Adipose Tissue; Adiposity; Adult; Anthropometry; Female; Gene Expression Regulation; Humans; Inflammation; Linear Models; Menopause; Middle Aged; Overweight; TNF-Related Apoptosis-Inducing Ligand

Levels of circulating TNF-related apoptosis-inducing ligand in celiac disease. - Celeghini, Claudio; Not, Tarcisio; Norcio, Alessia; Monasta, Lorenzo; Secchiero, Paola (Exp Ther Med, 2014)
It has previously been demonstrated that the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL) are significantly lower in patients with type 1 diabetes (T1D) than in normal age- and gender-matched controls. Since celiac disease (CD) is often associated with T1D, a retrospective study was performed to analyze the sera of a cohort of pediatric subjects: i) patients with CD at onset (n=100); ii) patients with potential CD (n=45); iii) patients with CD associated with other auto-immune diseases (n=17); and iv) patients with eosinophilic esophagitis (n=15). Among the patients with CD, 49 were also analyzed after six months on a gluten-free diet, while data were also available for 13 patients after one year on a gluten-free diet. No significant differences were found in the circulating levels of TRAIL between the patients with CD and the patients with either eosinophilic esophagitis or potential CD. Patients with CD associated with other auto-immune diseases showed significantly lower levels of TRAIL when compared with patients with CD alone. The gluten-free diet did not significantly modify the levels of circulating TRAIL at 6 or 12 months. Thus, although T1D and CD share common immunological features, the circulating levels of TRAIL show a significant difference between the two pathologies, and do not appear to be modulated in CD.

NF-κB pathways in hematological malignancies. - Gasparini, Chiara; Celeghini, Claudio; Monasta, Lorenzo; Zauli, Giorgio (Cell Mol Life Sci, 2014)
The nuclear factor κB or NF-κB transcription factor family plays a key role in several cellular functions, i.e. inflammation, apoptosis, cell survival, proliferation, angiogenesis, and innate and acquired immunity. The constitutive activation of NF-κB is typical of most malignancies and plays a major role in tumorigenesis. In this review, we describe NF-κB and its two pathways: the canonical pathway (RelA/p50) and the non-canonical pathway (RelB/p50 or RelB/p52). We then consider the role of the NF-κB subunits in the development and functional activity of B cells, T cells, macrophages and dendritic cells, which are the targets of hematological malignancies. The relevance of the two pathways is described in normal B and T cells and in hematological malignancies, acute and chronic leukemias (ALL, AML, CLL, CML), B lymphomas (DLBCLs, Hodgkin's lymphoma), T lymphomas (ATLL, ALCL) and multiple myeloma. We describe the interaction of NF-κB with the apoptotic pathways induced by TRAIL and the transcription factor p53. Finally, we discuss therapeutic anti-tumoral approaches as mono-therapies or combination therapies aimed to block NF-κB activity and to induce apoptosis (PARAs and Nutlin-3).
Keywords: Antineoplastic Agents; B-Lymphocytes; Carcinogenesis; Dendritic Cells; Gene Expression Regulation, Neoplastic; Hematologic Neoplasms; Humans; Imidazoles; Macrophages; NF-kappa B; Piperazines; Signal Transduction; T-Lymphocytes; TNF-Related Apoptosis-Inducing Ligand; Transcription Factor RelA; Transcription Factor RelB; Tumor Suppressor Protein p53

Potential role of circulating microRNAs as early markers of preeclampsia. - Ura, Blendi; Feriotto, Giordana; Monasta, Lorenzo; Bilel, Sabrine; Zweyer, Marina; Celeghini, Claudio (Taiwan J Obstet Gynecol, 2014)
OBJECTIVE: To identify microRNAs (miRNAs) differentially expressed at early stages of gestation (12-14 weeks) in the serum of pregnant women, who later developed severe preeclampsia (sPE) in the third trimester of pregnancy (n = 24) compared to women with normal pregnancy (n = 24). MATERIALS AND METHODS: Sera from 12-14-week-gestation whole blood were subjected to microarray analysis with TaqMan Low Density Array chips (human microRNA panel V3.0), and to quantitative real-time polymerase chain reaction. RESULTS: By using the TaqMan Low Density Array chip technology, 19 mature miRNAs appeared differentially expressed in the group of women who later developed sPE as compared to normal women. The expression of four miRNAs (miR-1233, miR-520, miR-210, miR-144) was validated by quantitative real-time polymerase chain reaction analysis. MiR-1233 was the most overexpressed in the serum of women who later developed sPE. CONCLUSION: Circulating miRNAs deserve further investigation in order to explore their potential role in the pathogenesis of preeclampsia. In particular, miR-1233 might represent a potential marker of early sPE.
Keywords: Adult; Biomarkers; Female; Gestational Age; Humans; MicroRNAs; Oligonucleotide Array Sequence Analysis; Pilot Projects; Pre-Eclampsia; Pregnancy; Retrospective Studies

Sodium dichloroacetate exhibits anti-leukemic activity in B-chronic lymphocytic leukemia (B-CLL) and synergizes with the p53 activator Nutlin-3. - Agnoletto, Chiara; Melloni, Elisabetta; Casciano, Fabio; Rigolin, Gian Matteo; Rimondi, Erika; Celeghini, Claudio; Brunelli, Laura; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
The anti-leukemic activity of the mitochondria-targeting small molecule sodium dichloroacetate (DCA), used alone and in association with the small molecule inhibitor of the p53/MDM2 interaction Nutlin-3, was analyzed in primary B-chronic lymphocytic leukemia (B-CLL) samples (n=22), normal peripheral blood cells (n=10) and in p53wild-type EHEB, JVM-2, JVM-3 B lymphoblastoid cell lines. DCA exhibited a dose-dependent anti-leukemic activity in both primary B-CLL and B leukemic cell lines with a functional p53 status and showed a synergistic cytotoxic activity when used in combination with Nutlin-3. At the molecular level, DCA positively regulated p53 activity, as documented by post-transcriptional modifications of p53 protein and synergized with Nutlin-3 in increasing the expression of the p53-target genes MDM2, PUMA, TIGAR and in particular p21. The potential role of p21 in mediating the DCA+Nutlin-3 anti-leukemic activity was underscored in knocking-down experiments. Indeed, transfection of leukemic cells with p21 siRNAs significantly decreased the DCA+Nutlin-3-induced cytotoxicity. Taken together, our data emphasize that DCA is a molecule that merits to be further evaluated as a chemotherapeutic agent for B-CLL, likely in combination with other therapeutic compounds.
Keywords: Aged; Aged, 80 and over; Dichloroacetic Acid; Drug Synergism; Female; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Middle Aged; Piperazines; Tumor Suppressor Protein p53

Soluble TRAIL is present at high concentrations in seminal plasma and promotes spermatozoa survival. - Zauli, Giorgio; Celeghini, Claudio; Monasta, Lorenzo; Martinelli, Monica; Luppi, Stefania; Gonelli, Arianna; Grill, Vittorio; Ricci, Giuseppe; Secchiero, Paola (Reproduction, 2014)
The expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL(TNFSF10)) and of its receptors (TRAILR1, TRAILR2, TRAILR3, and TRAILR4) have been documented in testis, but the presence of soluble TRAIL in seminal fluid, as well as the potential physiopathological role of the TRAIL/TRAILR system in spermatozoa, has not been previously investigated. Male donors (n=123) among couples presenting for infertility evaluation were consecutively enrolled in this study. The presence of soluble TRAIL was analyzed in seminal samples by ELISA, while the surface expression of TRAIL receptors was investigated by flow cytometry. High levels of soluble TRAIL were detected in seminal plasma (median, 11 621 pg/ml and mean±s.d., 13 371±8367 pg/ml) and flow cytometric analysis revealed a variable expression of TRAIL receptors in the sperm cellular fraction among different subjects. In addition, the effect of physiologically relevant concentrations of recombinant TRAIL was investigated on survival and motility of spermatozoa. Of interest, the in vitro exposure of capacitated spermatozoa to recombinant TRAIL (10 ng/ml) significantly preserved their overall survival. Therefore, the present study demonstrates for the first time the presence of elevated levels of the anti-inflammatory cytokine TRAIL in seminal fluids. Moreover, the demonstration that recombinant TRAIL promotes spermatozoa survival after capacitation suggests potential therapeutic implications.
Keywords: Adult; Apoptosis; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; Humans; Infertility, Male; Male; Receptors, TNF-Related Apoptosis-Inducing Ligand; Semen; Sperm Capacitation; Sperm Motility; Spermatozoa; TNF-Related Apoptosis-Inducing Ligand

Anti-leukemic activity of dasatinib in both p53(wild-type) and p53(mutated) B malignant cells. - Bosco, Raffaella; Rabusin, Marco; Voltan, Rebecca; Celeghini, Claudio; Corallini, Federica; Capitani, Silvano; Secchiero, Paola (Invest New Drugs, 2012)
The multi-kinase inhibitor dasatinib induced a variable but significant decrease of viability in both p53(wild-type) (EHEB, JVM-2, JVM-3) and p53(mutated) (MEC-1, MEC-2, BJAB) prolymphocytic B leukemic cells, due to a combination of cell cycle block in G1 and apoptosis. Antibody phospho-kinase array analysis revealed that dasatinib inhibited the phosphorylation of various kinases, including ERK1/2 and p38/MAPK as well as of STAT3 transcription factors, in both p53(wild-type) and p53(mutated) cells. Therefore, dasatinib might offer a novel therapeutic strategy not only for p53(wild-type), but also for p53(mutated) B malignancies that have the worst prognosis and urgently need innovative therapeutic approaches.
Keywords: Antineoplastic Agents; Apoptosis; B-Lymphocytes; Cell Line, Tumor; Cell Survival; G1 Phase Cell Cycle Checkpoints; Granulocyte Precursor Cells; Humans; Leukemia, Prolymphocytic, B-Cell; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Mutation; p38 Mitogen-Activated Protein Kinases; Phosphorylation; Protein Kinase Inhibitors; Pyrimidines; STAT3 Transcription Factor; Thiazoles; Time Factors; Tumor Suppressor Protein p53

Hydrogen sulfide down-regulates the expression and release of osteoprotegerin (OPG) by vascular endothelial cells. - Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Celeghini, Claudio; Secchiero, Paola; Zauli, Giorgio (Invest New Drugs, 2012)
Keywords: Cell Death; Cytostatic Agents; Down-Regulation; Human Umbilical Vein Endothelial Cells; Humans; Hydrogen Sulfide; Osteoprotegerin; Tumor Necrosis Factor-alpha

MCL1 down-regulation plays a critical role in mediating the higher anti-leukaemic activity of the multi-kinase inhibitor Sorafenib with respect to Dasatinib. - Secchiero, Paola; Melloni, Elisabetta; Voltan, Rebecca; Norcio, Alessia; Celeghini, Claudio; Zauli, Giorgio (Br J Haematol, 2012)
Keywords: Antineoplastic Agents; Benzenesulfonates; Cell Line, Tumor; Down-Regulation; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Protein Kinase Inhibitors; Proto-Oncogene Proteins c-bcl-2; Pyridines; Pyrimidines; Thiazoles

The sorafenib plus nutlin-3 combination promotes synergistic cytotoxicity in acute myeloid leukemic cells irrespectively of FLT3 and p53 status. - Zauli, Giorgio; Celeghini, Claudio; Melloni, Elisabetta; Voltan, Rebecca; Ongari, Manuele; Tiribelli, Mario; di Iasio, Maria Grazia; Lanza, Francesco; Secchiero, Paola (Haematologica, 2012)
BACKGROUND: Both the multi-kinase inhibitor sorafenib and the small molecule inhibitor of the MDM2/p53 interaction, nutlin-3, used alone, have shown promising anti-leukemic activity in acute myeloid leukemia cells. Thus, in this study we investigated the effect of the combination of sorafenib plus nutlin-3 in acute myeloid leukemia. DESIGN AND METHODS: Primary acute myeloid leukemia blasts (n=13) and FLT3(wild-type)/p53(wild-type) (OCI-AML3), FLT3(mutated)/p53(wild-type) (MOLM), FLT3(mutated)/p53(mutated) (MV4-11), FLT3(wild-type)/p53(deleted) (HL60) or FLT3(wild-type)/p53(mutated) (NB4) acute myeloid cell lines were exposed to sorafenib, used alone or in association with nutlin-3 at a 1:1 ratio, in a range of clinically achievable concentrations (1-10 μM). Induction of apoptosis and autophagy was evaluated by transmission electron microscopy and by specific flow cytometry analyses. The levels of Mcl-1, p53 and Bak proteins were analyzed by western blotting. Knock-down of Bax and Bak gene expression was performed in transfection experiments with specific short interfering RNA. RESULTS: The sorafenib+nutlin-3 drug combination exhibits synergistic cytotoxicity in primary acute myeloid leukemia blasts and in acute myeloid leukemia cell lines with maximal cytotoxicity in FLT3(mutated) MV4-11 and MOLM, followed by the FLT3(wild-type) OCI-AML3, HL60 and NB4 cell lines. The cytotoxic activity of sorafenib+nutlin-3 was characterized by an increase of both apoptosis and autophagy. Moreover, Bax and Bak showed prominent roles in mediating the decrease of cell viability in response to the drug combination in p53(wild-type) OCI-AML3 and p53(deleted) HL-60 cells, respectively, as demonstrated in transfection experiments performed with specific short interfering RNA. CONCLUSIONS: Our data demonstrate that acute myeloid leukemia cells show a variable but overall good susceptibility to the innovative therapeutic combination of sorafenib+nutlin-3, which differentially involves the pro-apoptotic Bcl-2 family members Bax and Bak in p53(wild-type) and p53(deleted) cells.
Keywords: Antineoplastic Agents; Drug Synergism; Female; fms-Like Tyrosine Kinase 3; HL-60 Cells; Humans; Imidazoles; Leukemia, Myeloid, Acute; Male; Niacinamide; Phenylurea Compounds; Piperazines; Tumor Suppressor Protein p53

Recent advances in the therapeutic perspectives of Nutlin-3. - Secchiero, Paola; Bosco, Raffaella; Celeghini, Claudio; Zauli, Giorgio (Curr Pharm Des, 2011)
Nutlin-3 is a small molecule inhibitor of the MDM2/p53 interaction, which leads to the non-genotoxic p53 stabilization, activation of cell cycle arrest and apoptosis pathways. A series of recent studies have strengthened the concept that selective, non-genotoxic p53 activation by Nutlin-3 might represent an alternative to the current cytotoxic chemotherapy, in particular for pediatric tumors and for hematological malignancies, which retain a high percentage of p53(wild-type) status at diagnosis. Like most other drugs employed in cancer therapy, it will be unlikely that Nutlin-3 will be used as a monotherapy. In this respect, Nutlin-3 shows a synergistic cytotoxic effect when used in combination with innovative drugs, such as TRAIL or bortozemib. Although Nutlin-3 is currently in phase I clinical trial for the treatment of retinoblastoma, its effects on normal tissues and cell types remain largely to be determined and will require further investigation in the future years.
Keywords: Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Drug Synergism; Genes, p53; Humans; Imidazoles; Neoplasms; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53

Trail down-regulates the release of osteoprotegerin (OPG) by primary stromal cells. - Corallini, Federica; Celeghini, Claudio; Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Secchiero, Paola; Zauli, Giorgio (J Cell Physiol, 2011)
The soluble member of the TNF-R superfamily osteoprotegerin (OPG) is abundantly released under basal conditions by both mesenchymal stem cells (MSC) and fibroblasts and by endothelial cells upon stimulation with inflammatory cytokines. Since MSC, fibroblasts and endothelial cells represent key elements of the normal and tumor microenvironment and express detectable levels of surface TRAIL receptors, we investigated the effect of TRAIL on OPG release. Unexpectedly, recombinant TRAIL decreased the spontaneous OPG release in all cell types examined. Moreover, TRAIL decreased OPG release also in stromal cells co-cultured with lymphoma cells and counteracted the OPG induction by TN-alpha in HUVEC and MSC. Such down-regulation was not due to a masking effect in the ELISA quantification of the OPG released in the culture supernatants due to binding of OPG to its ligands (TRAIL and RANKL), as demonstrated by competition experiments with recombinant TRAIL and by the lack of RANKL release/induction. In addition, OPG down-regulation was not due to induction of cytotoxic effects by TRAIL, since the degree of apoptosis in response to TRAIL was negligible in all primary cell types. With regards to the possible molecular mechanism accounting for the down-regulation of OPG release by TRAIL, we found that treatment of MSC with TRAIL significantly decreased the phosphorylation levels of p38/MAPK. There is a suggestion that this pathway is involved in the stabilization of OPG mRNA. In this respect, the ability of TRAIL to decrease the release of OPG, in the absence of cell cytotoxicity, was mimicked by the p38/MAPK inhibitor SB203580.
Keywords: Bone Marrow Cells; Cell Death; Cells, Cultured; Coculture Techniques; Down-Regulation; Endothelial Cells; Enzyme Activation; Enzyme-Linked Immunosorbent Assay; Fibroblasts; Humans; MAP Kinase Signaling System; Mesenchymal Stromal Cells; Osteoprotegerin; p38 Mitogen-Activated Protein Kinases; Protein Binding; Recombinant Proteins; Stromal Cells; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor-alpha

Treatment with recombinant tumor necrosis factor-related apoptosis-inducing ligand alleviates the severity of streptozotocin-induced diabetes. - Zauli, Giorgio; Toffoli, Barbara; di Iasio, Maria Grazia; Celeghini, Claudio; Fabris, Bruno; Secchiero, Paola (Diabetes, 2010)
OBJECTIVE: To evaluate the potential therapeutic effect of recombinant human tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) treatment in a model of type 1 diabetes. RESEARCH DESIGN AND METHODS: Recombinant TRAIL was added in vitro to primary human and mouse peripheral blood mononuclear cells (PBMCs) and isolated human islets to evaluate the expression of the immunoregulatory gene SOCS1. Diabetes was induced by five consecutive daily injections of low-concentration (50 mg/kg) streptozotocin (STZ) in C57 black mice (n = 24). A group of these mice (n = 12) was co-injected with recombinant TRAIL (20 microg/day) for 5 days, and the diabetic status (glycemia and body weight) was followed over time. After 6 weeks, circulating levels of insulin, TNF-alpha, and osteoprotegerin (OPG) were measured, and animals were killed to perform the histological analysis of the pancreas. RESULTS: The in vitro exposure of both PBMCs and human islets to recombinant TRAIL significantly upregulated the expression of SOCS1. With respect to STZ-treated animals, mice co-injected with STZ+TRAIL were characterized by 1) lower levels of hyperglycemia, 2) higher levels of body weight and insulinemia, 3) a partial preservation of pancreatic islets with normal morphology, and 4) a lower expression of both systemic (TNF-alpha and OPG) and pancreatic (vascular cell adhesion molecule [VCAM]-1) inflammatory markers. CONCLUSIONS: Overall, these data demonstrate that the administration of recombinant TRAIL ameliorates the severity of STZ-induced type 1 diabetes, and this effect was accompanied by the upregulation of SOCS1 expression.
Keywords: Animals; Cells, Cultured; Diabetes Mellitus, Experimental; Gene Expression; Humans; Islets of Langerhans; Leukocytes, Mononuclear; Mice; Recombinant Proteins; Suppressor of Cytokine Signaling Proteins; TNF-Related Apoptosis-Inducing Ligand